2014
DOI: 10.1093/humrep/det457
|View full text |Cite
|
Sign up to set email alerts
|

ESHRE guideline: management of women with endometriosis

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
1,692
1
185

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,848 publications
(1,902 citation statements)
references
References 93 publications
24
1,692
1
185
Order By: Relevance
“…While some women with endometriosis can experience painful symptoms and/or infertility, others have no symptoms at all. Susceptibility to endometriosis depends on a complex interaction of immunologic, genetic and hormonal factors [16].Theoretically, the recurrent lesions might originate from either residual lesions or de novo cells coming through retrograde bleeding. For the former assumption, several studies demonstrate that the recurrence risk increases if the lesions are not completely removed at the initial surgery and they tend to arise on the same location [17].Six months of GnRHa therapy immediately following surgery reduces the rate of symptom recurrence of endometriosis, and increases the length of time before symptoms recur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some women with endometriosis can experience painful symptoms and/or infertility, others have no symptoms at all. Susceptibility to endometriosis depends on a complex interaction of immunologic, genetic and hormonal factors [16].Theoretically, the recurrent lesions might originate from either residual lesions or de novo cells coming through retrograde bleeding. For the former assumption, several studies demonstrate that the recurrence risk increases if the lesions are not completely removed at the initial surgery and they tend to arise on the same location [17].Six months of GnRHa therapy immediately following surgery reduces the rate of symptom recurrence of endometriosis, and increases the length of time before symptoms recur.…”
Section: Discussionmentioning
confidence: 99%
“…Goserelinacetateis medicines that work by causing a temporary menopause. They are modified forms of GnRH that bind to receptors in the pituitary but have a longer half-life than native GnRH and thereby in down-regulation of the pituitary-ovarian axis and hyperestrogenism, The treatment causes the ovaries to stop producing estrogen, which causes the endometriosis implants to shrink [25].Murphy et al whofound increased oxidation of low-density lipoprotein and increased concentrations of oxidized low-density lipoproteins in the peritoneal fluid in patients with pelvic endometriosis. Oxidative modification of these molecules involves peroxidation of the lipid component, which leads to release of aldehydes, such as malondialdeyde [26].…”
Section: Discussionmentioning
confidence: 99%
“…Past diagnosis of endometriosis and surgical treatment details are particularly important in planning further management. Special consideration should be given to women who report significant dysmenorrhea and dyspareunia, and those who have signs (see below) of endometriosis on pelvic ultrasound [5]. Infertile women have on average a 30 % chance of endometriosis, rising to 50 % if dyspareunia is present.…”
Section: Workupmentioning
confidence: 99%
“…The European Society of Human Reproduction and Embryology guidelines state that there is no evidence that cystectomy prior to treatment with ART improves the pregnancy rates in infertile women with endometriomas that are >30 mm. The Guideline Development Group recommends that clinicians only consider cystectomy prior to ART to improve endometriosis‐associated pain or the accessibility of the follicles 8. In addition, it has been reported that surgery prior to scheduled ART does not benefit asymptomatic women with an endometrioma 9…”
Section: Introductionmentioning
confidence: 99%